(untitled) (Universal International Scientific Journal, 2026)
The article analyzes the functions of the heads of preschool educational organizations in organizing and managing methodological collaboration between teachers. In the modern education system, special attention is paid to the tasks of the head of the organization in coordinating methodological activities, directing the pedagogical team to professional development, creating a cooperative environment, and effectively managing methodological resources. The study scientifically substantiates the strategic planning, organizational pedagogical, control-analytical, motivational, and innovative functions of the head. The article shows modern approaches to the management of methodological collaboration by the head of the preschool educational organization, international experience, and the possibilities of their application to the preschool education system of Uzbekistan. The results of the study are of practical importance for heads of preschool educational organizations, methodological service employees, and specialists working on improving the preschool education system.